Estimation of maximal lactate steady state in trained female rowers - Mattern, C. O.; Gutilla, M. J.; Kirby, T. E.; Devor, S. T. (Journal of Exercise Physiology online, 2007)
Endurance training at intensities approximating maximal lactate steady state (MLSS) may heighten exercise adaptations while minimizing risk of overtraining. Measuring MLSS in the laboratory is labor intensive; however, time trial events are relatively simple and often completed in endurance sports. To determine if a relationship exists between the average workload during a 6 km rowing time trial and MLSS workload, female Division I rowers (age 20.1± 0.2yrs, VO2 peak 46.4±0.8ml/kg/min, n=23) underwent a maximal power output test on the rowing ergometer (max power 263.5 ± 5.9 W), and MLSS determined using 30 min constant workload bouts of rowing (mean MLSS 2.64 ± 0.1mmol/l). Subsequently, subjects completed a 6 km time trial to determine time and mean power. A significant relationship was found between mean power output and MLSS workload (r² =0.8377, p<.0001). Mean power output during the 6 km time trial (214.4 ± 4.8W) was greater than the average MLSS power output (168.6 ± 4.1W). Utilizing the regression equation: y = 0.7793x + 1.5041, where x = mean 6 km time trial workload and y = MLSS workload, individual MLSS intensity can be predicted. For rowers, as the time to complete a 6 km time trial decreases, MLSS workload increases. Results suggest that training to improve MLSS workload may improve 6 km time trial performance. ABSTRACT FROM AUTHOR